2014
DOI: 10.1371/journal.pone.0105810
|View full text |Cite
|
Sign up to set email alerts
|

Selenite Enhances Immune Response against Pseudomonas aeruginosa PA14 via SKN-1 in Caenorhabditis elegans

Abstract: BackgroundSelenium (Se) is an important nutrient that carries out many biological processes including maintaining optimal immune function. Here, inorganic selenite (Se(IV)) was evaluated for its pathogen resistance and potential-associated factors in Caenorhabditis elegans. The immune effects of Se(IV) were investigated by examining the responses of C. elegans to Pseudomonas aerugonisa PA14 strain.Principal FindingsSe(IV)-treated C. elegans showed increased survival under PA14 infection compared with untreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
(94 reference statements)
2
13
0
Order By: Relevance
“…This would mimic the effects exerted by a marine brown seaweed extract in overcoming the pathogenicity of PA14 towards C. elegans (Kandasamy et al, 2012). Alternately, H. atra could also contain compounds capable of directly inducing lys-7 activities, as reported elsewhere (Fatin et al, 2017; Li et al, 2014).…”
Section: Discussionsupporting
confidence: 56%
“…This would mimic the effects exerted by a marine brown seaweed extract in overcoming the pathogenicity of PA14 towards C. elegans (Kandasamy et al, 2012). Alternately, H. atra could also contain compounds capable of directly inducing lys-7 activities, as reported elsewhere (Fatin et al, 2017; Li et al, 2014).…”
Section: Discussionsupporting
confidence: 56%
“…Previous work has shown that skn‐1 mutants are vulnerable to oxidative stress, whereas skn‐1 overexpression afforded protection against manganese‐induced toxicity . Furthermore, selenite exposure of the nematode has been shown to enhance expression of gst‐4 as well as gcs‐1 under PA14 infection via SKN‐1 . Recently, Salgueiro et al.…”
Section: Resultsmentioning
confidence: 96%
“…In C. elegans selenite exerts beneficial effects on development, cholinergic signaling, and innate immune response (Li et al, 2011;Li et al, 2014a). At high concentrations, selenite can be harmful to C. elegans (Morgan et al, 2010;Estevez et al, 2012).…”
Section: Discussionmentioning
confidence: 99%